Full-Scale Testing and Theoretical Analysis of Influence of Tension Insulator Strings on the Sag of UHV Conductors - Gang SONG; Guohui SHEN; Yunan BAO; Fei TENG (Zhongguo dianli)
In order to study the influence of tension insulator string’s weight on the sags and tensions of ultra-high voltage (UHV) conductors, full-scale testing and theoretical analysis are carried out. The full-scale testing of sags of a three-span transmission line are conducted using global positioning system (GPS) and total stations, and the sag’s distribution characteristics of tension insulator strings and conductors are obtained. A theoretical analysis method is developed with consideration of the correlation between tension insulator string’s weight and conductor’s sags, and the horizontal tension forces of transmission lines are fitted based on the full-scale testing data. The results show that both the conductors and tension insulator strings have a shape of catenary curve in sag. When the tension insulator string’s weight is not considered, the fitting results differ significantly from the testing results, with the maximum discrepancy of fitting tension between the strain section and the straight section reaching 27%. When the tension insulator string’s weight is considered, the difference between fitting results and testing results is quite small, with the maximum discrepancy of fitting tension between strain section and straight section being only 1.7%. It can be seen that the influence of tension insulator string’s weight must be considered in determining the sag of a strain section of UHV transmission lines.